Urban form and life-cycle energy consumption: Case studies at the city scale - Nichols, Brice G.; Kockelman, Kara (Journal of Transport and Land Use, 2015)
By combining daily (operations) and embodied energy demands, this work estimates life-cycle energy demands for residents and workers in different city settings. Using life-cycle analyses (LCAs) of different neighborhood types in Austin, Texas, this analysis fabricates five different city types, reflecting actual accessibility and resident and employment density profiles. Five residential and three commercial neighborhood types are distributed across 16-kilometer (10-mile) radius regions, with demographics held constant, for comparability. As expected, per-capita daily energy demands decrease with increased resident and employment density. Interestingly, embodied energy savings via increases in density are substantial. Though embodied energy makes up only 10-20 percent of total life-cycle energy, per-capita savings via density suggest it should be included in planning analyses. Overall, average life-cycle per-capita energy use ranges from 140 gigajoule (GJ)/ year/capita in the least dense Orlando-style setting to around 90 GJ/ year/capita in the maximum-density scenario, corresponding to a 35 percent reduction in per-capita energy demand. Energy reductions for Phoenix, Austin, and Seattle settings (relative to an Orlando-based de- sign) are 18, 22, and 24 percent per-capita, respectively. Results provide a rare view of how total annual energy demands in both residential and commercial sectors are affected by density.